Model Radical Marketing and Customer Satisfaction Bank Jatim Branch Sememi Surabaya Region - Chandra Kartika; Chamariyah Chamariyah; Rena Febrita Sarie; Veronika Nugraheni Sri Lestari (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of the study is to test and analyze the Influence of Service Marketing, Referral Marketing, Trust Icon Corporate on Radical Marketing through Customer Satisfaction at Bank Jatim Sememi Branch Surabaya. Design/methodology/approach: Purposive Sampling Method. The total sample of 100 Customer Respondents at Bank Jatim Sememi Branch. This research is a Survey Research and Quantitative approach. The data analysis technique of this study uses the Partial Least Square (PLS) method. Findings: The results of Service Marketing Research do not directly affect Customer Satisfaction, Referral Marketing has a direct effect on Customer Satisfaction, Trust Icon Corporate does not directly affect Customer Satisfaction, Service Marketing has a direct effect on Radical Marketing, Referral Marketing has a direct effect on Radical Marketing, Trust Icon Corporate directly affects Radical Marketing. Service Marketing does not have an indirect effect on Radical Marketing through Customer Satisfaction. Radical Marketing does not have an indirect effect on Radical Marketing through Customer Satisfaction. Trust Icon Corporate does not indirectly affect Radical Marketing through Customer Satisfaction. Originality/value: This paper is original Paper type: Research paper